Effect of dielectric barrier discharge cold plasma on the bruise susceptibility of plum fruit. (4th November 2022) - Rashvand, Mahdi; Hajizadeh, Ali; Akbarnia, Abbas; Abbaszadeh, Rouzbeh; Nikzadfar, Mehrad; Pathare, Pankaj B.
Abstract: Tissue firmness is one of the most important factors in consuming fresh fruits. The firmness of the plum is the main parameter to purchase. This study aimed to investigate the effect of the dielectric barrier discharge (DBD) cold plasma method on the mechanical properties of plums during storage time. For this purpose, a tesla system and cold plasma generation by DBD were used. Plums were treated by plasma three times for 5, 10 and 15 min and then evaluated in five periods 1st, 5th, 10th, 15th and 20th days. Also, the simulation method was used to measure the plums' bruise volume (BV) and bruise susceptibility (BS). The simulated and experimental BV and BS values were compared, and the maximum relative difference were 13.12% and 10.18%, respectively. In addition, scanning electron microscopy (SEM) was utilized to investigate the microstructure of the tissue before and after the drop test. The results revealed that the DBD treatment of 5 and 15 min had a negative effect on the mechanical properties of the plums. While the DBD treatment of 10 had an acceptable impact on the trend of Young's modulus, bio yield stress, and tangent modulus during the storage time. This treatment enhances the resistance of the plums to deformation and reduces the BV and BS tendency caused by impact. Practical Applications: Mechanical damage of fresh fruits in the postharvest process by processing plants reduces the quality of the product in terms of firmness. Therefore, customers are reluctant to buy products with unacceptable rigidity. Plum is one of the expensive fruits that is always influenced by mechanical damage in the procedure of processing such as sorting. Therefore, it seems necessary to provide a solution that maintains firmness and does not affect the chemical quality of the product. DBD cold plasma is an economical, fast and reliable method to maintain the firmness of fresh fruits. Although DBD cold plasma can preserve the mechanical properties of the fruits by disinfection, treatment time can have both positive and negative effects. In other words, the over‐treatment time sometimes causes fruit tissue to loosen or low‐treatment time has been no significant difference. Therefore, it seems research on the effect of treatment time is essential. The results of this study can be useful for horticultural processing plants to increase fruit quality in terms of firmness. Abstract :